PERSONALIZATION OF PROFESSIONAL DEVELOPMENT OF UNIVERSITY PEDAGOGICAL STAFF - Vyacheslav A. Starodubtsev; Evgenia V. Isaeva (Высшее образование в России)
Abstract. With the rapid updating of knowledge and technologies, a shift is necessary from shortBterm courses of improvement of university teaching staff qualification to a system of continuous professional development, combining a system of practiceBoriented courses of formal (academic) refresher training and informal methodological support of teaching staff as the developers of discipline content, training tools and methods of interaction. Personal professional development routes are implemented within modular programmes of further education, after peer to peer evaluation, taking into account the individual needs of the Faculty and the University’s programme of innovation development priorities. Personal educational results achieved in the professional development system are evaluated by means of educational products created in the course of additional educational program selected.